2021
DOI: 10.18844/wjet.v13i4.6313
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of disabled university students on the distance education process

Abstract: The purpose of this research is to evaluate the views of university students with disabilities, regarding the distance education process. The data collection tool of this qualitative research carried out in a phenomenological design is a semi-structured interview form developed by the researcher, which aims to get the opinions of the disabled students studying at the university on the distance education process. The study group of the research consists of 30 students with visual, hearing and orthopedic disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Online learning can make it easier for older adults with disabilities to study at university by enabling them to combine their studies with employment and family commitments (McManus et al, 2017). However, the studies by McManus et al (2017) and Stambekova et al (2021) identified a number of barriers to studying in the online context. Thus, students with disabilities who participated in the study of McManus et al (2017) did not find it easy to study while balancing their family obligations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online learning can make it easier for older adults with disabilities to study at university by enabling them to combine their studies with employment and family commitments (McManus et al, 2017). However, the studies by McManus et al (2017) and Stambekova et al (2021) identified a number of barriers to studying in the online context. Thus, students with disabilities who participated in the study of McManus et al (2017) did not find it easy to study while balancing their family obligations.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the advantages of online learning in terms of being able to study anywhere and with time flexibility, studies highlighted the absence of face-to-face interaction, both faculty-student and student-student, as a negative aspect (McManus et al, 2017; Stambekova et al, 2021). In the case of people with mental disabilities, this caused feelings of isolation and disconnection.…”
Section: Resultsmentioning
confidence: 99%
“…Educational systems are expected to meet the socio-cultural, developmental, and individual needs of all individuals around the world. However, university students with special needs may experience problems in different areas such as education, accessibility, and participation (Stambekova et al, 2021). The present study focused on the university experiences of students with special needs and their suggestions for the problems they had experienced.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…2020;Altun Ekiz, 2020;Kılıç, 2020;Mahdy, 2020;Ramos-Morcillo, et Al. 2020;Stambekova, et Al., 2021;Topuz et Al., 2021;Yağan, 2021;Yılmaz, 2020;Yolcu, 2020). It can be claimed that studies analyzing the opinions of faculty members about emergency remote teaching during the pandemic period are relatively few in number compared to studies examining student opinions (Almaghaslah & Alsayari, 2020;Altınpulluk, 2021;Elberkawi, et Al.…”
Section: Introductionmentioning
confidence: 99%